Determinants of Value Benefits in Adopting an Engineering Procurement and Construction Management (EPCM) – ABU DHABI Oil and Gas, UAE - ALZAABI, ABDULLA RASHED (2022)
The requirement for modern businesses to develop complex projects has forced businesses to consider opportunities for application of specific contracting models which would guarantee adequate distribution of responsibility in the project team among stakeholders and minimise risks for the project owner. This study aims to analyse the main characteristics of the EPC and EPCM contracting models for the Abu Dhabi oil and gas sector, and determine opportunities and risks related to the application of both contracting models. Specific results had to be associated with the definition of optimal guidelines for application of the EPCM contracting model in the target sphere of practice. The results of the prior literature review demonstrated that, though the EPCM contracting model is generally considered as more effective compared to the EPC approach, practitioners lack reliable recommendations for application of this method in practice. The methodology of the thesis included a quantitative study of a large sample of employees and managers in the target industry to gain understanding of their perception of the EPCM contracting model. The results of the study demonstrate the main features and factors of successful application of the EPCM contracting model in the target industry, together with practical guidelines for future implementation. It was found that the EPCM contracting model could be the optimal approach to large project management if properly arranged. The novelty of this research can be viewed from two perspectives:  One is from a theoretical point of view where the research will challenge existing theories of value and contracting strategies. The research proposes ways in which value and contracting strategies and theories can be enhanced within the context of the oil and gas sector.  Two, from a practical point of view, the research ascertained key practical EPCM determinants which can be used as guidelines for senior project practitioners in delivering large oil and gas programmes and mega projects in Abu Dhabi for better value through using the EPCM model.